SOCIO-DEMOGRAPHY, SUBSTANCE ABUSE AND OFFENCE AMONG INMATES WITH PSYCHIATRIC DISORDERS IN FEMALE JUVENILE CENTRE, BANGLADESH - Maruf, Mohammad Muntasir; Rahman, Farzana; Khan, Muhammad Zillur; Jahan, Nasim (PEOPLE: International Journal of Social Sciences, 2015)
Inmates of Juvenile Developmental Centers are generally vulnerable to psychiatric illness. Females are more prone to that. The objective of the study was to determine the socio-demographic correlates, prevalence of substance abuse and offence among female inmates with psychiatric disorders in Juvenile Development Center. This was a cross sectional and descriptive study conducted in Juvenile Developmental Center (Girls’), Bangladesh. All female inmates of 9 to 18 years of age were enrolled in the study. Total respondents were 43. One stage-structured assessment of psycho-pathology was carried out by using a structured and valid Bangla version of The Development and Well-Being Assessment (DAWBA). Information regarding socio-demography, substance abuse and offence was collected through face-to-face interview with a semi-structured questionnaire and case-notes. Data analysis was done by SPSS for windows 15 version. The result revealed that overall prevalence of psychiatric disorder was 93% in inmates of Juvenile Developmental Center. Among the respondents with psychiatric disorders, 10% had history of substance abuse and 30% had history of offence. It can be concluded that considerable rate of substance abuse and offence was there among the female juvenile with psychiatric disorders in the development centre. Considering limitations, careful conclusion should be drawn.